ANTIMICROBIAL ACTIVITY SCREENING OF M. MINUTA EXTRACTS - A. R., Bindu; Jose, Rosemary; S., Akhila (International Journal of Pharmacy and Pharmaceutical Sciences, 2014)
Objective: Infectious diseases are a leading cause of global disease burden with high morbidity and mortality especially in the developing world. Furthermore, there have been threats of new diseases during the past three decades due to the evolution and adaptation of microbes and the re-emergence of old diseases due to the development of antimicrobial resistance and the capacity to spread to new geographic areas. Since antiquity, humans have used plants to treat common infectious diseases and some of these traditional medicines are still included as part of the habitual treatment of various maladies. Objective of the study was to evaluate, one of the traditionally used drugs, Marselia minuta for its antimicrobial activity. Methods: Extracts of M. minuta was prepared using successive solvent extraction method and the antibacterial activity of thus prepared petroleum ether, chloroform, ethyl acetate, alcohol and aqueous extracts of M. minuta was performed using agar well diffusion method. Four bacterial strains were used to assess the antimicrobial properties of the plant extracts viz Escherichia coli, Streptococcus pneumonia, Pseudomonas aeruginosa and Staphylococcus aureus. Results: All the extracts showed activity towards the tested microorganisms except petroleum ether extract. Ethyl acetate extract was more active towards S. aureus and P. aeruginosa. Alcohol and chloroform extract was active toward E. coli and P. aeruginosa. Aqueous extract was active against E. coli and S. aureus. minimum inhibitory concentration were calculated for each extract and the Significant activity was observed for ethyl acetate extract (E. coli-11.33 mm, S. aeruginosa-16.0 mm) and alcoholic fractions (E. coli-15.33 mm and P. aeruginosa-10.66 mm) for concentration 500 mcg/ml. Conclusion: Thus, the result in the present experiment ensures the traditional use of M. minuta as antibacterial agent. Further, the most active extracts can be subjected for isolation of the therapeutic antimicrobials and its formulation which will be relatively safer than synthetic medicines and offering profound therapeutic benefits at the more affordable price.